Enhanced mate tea (Ilex paraguariensis): A novel blend with Brazilian native fruits (pitanga and jabuticaba) for health and flavor - GOBBI, Bruna Gomes das Virgens; LIMA, Sarah Nicolle Carvalho de; GATTO, Natalia; COELHO, Silvia Renata Machado; PRADO, Naimara Vieira do; WAGNER JÚNIOR, Américo; LUCCHETTA, Luciano (Food Science and Technology, 2025)
Mate tea (MT) (Ilex paraguariensis) can be consumed hot or cold, with the latter often enhanced with fruits, making it a popular choice for health-conscious consumers. This study aimed to develop a MT beverage combined with dehydrated pitanga (Eugenia uniflora L.) and jabuticaba (Plinia trunciflora O. Ber), both rich in nutrients. Different quantities of these fruits (up to 30%) were tested in combination with MT, analyzing parameters like total soluble solids (Brix), acidity, pH, color, total phenolic compounds, and tannins. The addition of jabuticaba and pitanga increased soluble solids, decreased pH, and raised acidity. Color changes were influenced by both fruits, with jabuticaba increasing luminosity. Although the standard MT had higher tannin and phenolic content, the addition of fruits still maintained significant levels of phenolic compounds, albeit reduced. Principal component analysis (PCA) highlighted MT’s impact on phenolic composition, and overall, the addition of jabuticaba and pitanga improved the beverage’s color and soluble solids content, despite a phenolic reduction.